Transcatheter Arterial Embolization for Palliation of Uterine Body Cancer Bleeding - Jaeyeon Choi; Ji Hoon Shin; Hee Ho Chu (Journal of the Korean Society of Radiology, 2023)
Purpose This study aimed to evaluate the efficacy and safety of transcatheter arterial embolization (TAE) for bleeding due to uterine body cancer. Materials and Methods In this retrospective study, six patients with varying types of uterine body cancer who underwent TAE for bleeding control were investigated. Angiographic findings, cross-sectional images, TAE details, and clinical outcomes were studied. Technical and clinical success rates were calculated. Results The identified patients had endometrioid adenocarcinoma, sarcoma, and gestational trophoblastic neoplasia, and most were patients with advanced-stage cancer. In four patients, tumor bleeding presented as vaginal bleeding. Technical success was achieved in all seven TAE procedures in six patients. Two patients with recurrent masses who had undergone hysterectomy presented with hematochezia, and TAE was able to provide technical success in these patients as well. The clinical success rate was 50%, indicating bleeding control for > 1 week. Rebleeding was directly associated with death in one patient. On the following day, mild fever was observed in one patient. Conclusion TAE can be considered an effective and safe method of bleeding control for uterine body cancer, especially during critical periods throughout the disease course of patients with inoperable, advanced-stage cancer.